PERBANDINGAN PENDAPATAN PETANI PADI SAWAH VARIETAS PANDAN WANGI DAN ANGKE MENGGUNAKAN METODE SYSTEM OF RICE INTENSIFICATION (SRI) DI DESA LUTHU LAMWEU KECAMATAN SUKA MAKMUR KABUPATEN ACEH BESAR - Dara Angreka Soufyan (Universitas Teuku Umar, 2016)
Globally, rice is one of the most food crops for human cosumption. For livestock feed, rice production needs to be increased. In order to increase grain yield, productivity SRI is one of the other intensif achievement. The purpose of this study is to compare the revenue of Farmer who is using Pandan Wangi and Angkevarietie in LuthuLamweu village, SukaMakmur sub-distict, Aceh Besar. The population were 23 farmers which is 9 farmers ofPandan Wangi and 14 farmers of Angke. This study is using T-test for testing the hypothesis. The result for the T-test= 9.148 is higher than T-table and the average income for farmers ofPandan Wangi is Rp 835.316,- and minus Rp392.029,-farmers of Angke